Análise anátomo-radiográfica com determinação do tempo de trânsito gastrintestinal em tigre d água brasileiro Trachemys dorbignyi Duméril e Bibron, 1835 e tigre d americano Trachemys scripta elegans Wied, 1838 (Testudines, Emydiae) Wied, 1838 (Testudines, Emydidae) - Moraes, Flávio Machado de (2007)
Trachemys dorbignyi and Trachemys scripta elegans are herbivores, but they can also feed on minor quantities of food of animal origin. The speed of digestion of these animals is affected by temperature and diet. Studies of the gastrointestinal transit time are required in order to understand the digestive processes of foods in the animal organism. An evaluation was made of radiographic anatomical aspects and the gastrointestinal transit time of this reptile, which is information required in the clinical treatment of wild animals. The study involved 21 animals, one of which a female was destined for the preparation of an anatomical model to describe the gastrointestinal tract. The other 20 animals, comprising 10 Trachemys dorbignyi (6 males and 4 females) and 10 Trachemys scripta elegans (3 males and 7 females) and weighing on average 1.23 kg, came from the Federal University of Uberlândia s Wild Animal Research Laboratory. The animals were given a 10mL/Kg dose of barium sulfate suspension (Bariogel®) mixed with mineral oil (Nujol®) in a proportion of 70% barium sulfate to 30% oil administered orally. The specimens were then radiographed at predetermined time intervals in the dorsoventral position, with the X-ray machine set at 72 Kv and 200 mA. On average, the stomach became filled ten minutes after administration of the contrast. With regard to the small intestine, it was found that the duodenal region was filled with barium sulfate after 10 minutes, while the cecum took from 24 hours to 2 days to fill up, as did the colon and rectum. Complete emptying of the stomach occurred between radiographic exposure 3 (equivalent to 6 hours) and 4 (equivalent to 12 hours). Elimination of the radiographic contrast material by the small intestine occurred between the 1st and 5th day, while emptying of the colon/rectum occurred between the 2nd and 11th day. Total elimination of the contrast took on average 6.26 days, with a minimum of 2 days and a maximum of 11 days.